STRATEGI PELESTARIAN TRADISI JAMASAN PUSAKA SUROLOYO SEBAGAI ASET BUDAYA TRADISIONAL DI KULON PROGO YOGYAKARTA - Sarbini Sarbini; Indri Shaila Hapsari (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
This research aims to determine how the strategy of preserving the Jamasan Pusaka Suroloyo tradition as a traditional cultural asset in Kulon Progo Yogyakarta. The research method uses qualitative research and data analysis uses SWOT analysis. This research was conducted in September-October 2019. Based on the research conducted, researchers found that the preservation of the Jamasan Pusaka tradition in Suroloyo is the only Jamasan Pusaka tradition in Kulon Progo. The Jamasan Pusaka tradition in Suroloyo is held at the Suroloyo Peak Tourism Object on the 1st of Suro. In an effort to preserve the Jamasan tradition, it can be said that the community still carries out this tradition today. In addition, managers and the community have played an important role in the Jamasan Pusaka Tradition and the Government has been very helpful in preserving the Jamasan Pusaka Tradition.Keywords: Jamasan Pusaka Tradition, Preservation, Tourism Culture, SWOT Analysis